Genetic Diversity of Viral Populations Associated with Ananas Germplasm and Improvement of Virus Diagnostic Protocols - Adriana E. Larrea-Sarmiento; Alejandro Olmedo-Velarde; Xupeng Wang; Wayne Borth; Ryan Domingo; Tracie K. Matsumoto; Jon Y. Suzuki; Marisa M. Wall; Michael J. Melzer; John Hu (Pathogens, 2022)
Pineapple (Ananas comosus L. [Merr.]) accessions from the U.S. Tropical Plant Genetic Resources and Disease Research (TPGRDR) in Hilo, Hawaii were subjected to RNA-sequencing to study the occurrence of viral populations associated with this vegetatively propagated crop. Analysis of high-throughput sequencing data obtained from 24 germplasm accessions and public domain transcriptome shotgun assembly (TSA) data identified two novel sadwaviruses, putatively named “pineapple secovirus C” (PSV-C) and “pineapple secovirus D” (PSV-D). They shared low amino acid sequence identity (from 34.8 to 41.3%) compared with their homologs in the Pro-pol region of the previously reported PSV-A and PSV-B. The complete genome (7485 bp) corresponding to a previously reported partial sequence of the badnavirus, pineapple bacilliform ER virus (PBERV), was retrieved from one of the datasets. Overall, we discovered a total of 69 viral sequences representing ten members within the Ampelovirus, Sadwavirus, and Badnavirus genera. Genetic diversity and recombination events were found in members of the pineapple mealybug wilt-associated virus (PMWaV) complex as well as PSVs. PMWaV-1, -3, and -6 presented recombination events across the quintuple gene block, while no recombination events were found for PMWaV-2. High recombination frequency of the RNA1 and RNA2 molecules from PSV-A and PSV-B were congruent with the diversity found by phylogenetic analyses. Here, we also report the development and improvement of RT-PCR diagnostic protocols for the specific identification and detection of viruses infecting pineapple based on the diverse viral populations characterized in this study. Given the high occurrence of recombination events, diversity, and discovery of viruses found in Ananas germplasm, the reported and validated RT-PCR assays represent an important advance for surveillance of viral infections of pineapple.